Prepubertal Glucocorticoid Status and Pubertal Timing - Shi, Lijie; Wudy, Stefan A.; Buyken, Anette; Maser-Gluth, Christiane; Hartmann, Michaela F.; Remer, Thomas (The Journal of Clinical Endocrinology & Metabolism)
Context: Whether prepubertal glucocorticoid status impacts on the timing of puberty is not clear. Objective: The objective of the study was to examine the relationship between prepubertal glucocorticoid status and early or late pubertal markers, independent of adrenarchal and nutritional status. Design and Participants: Prospective cohort study of healthy Caucasian children (n = 111, 56 boys) who provided both 24-h urine samples and weighed dietary records 1 and 2 yr before the start of pubertal growth spurt [age at take-off (ATO)]. Measurements: Major urinary glucocorticoid and androgen metabolites determined by gas chromatography-mass spectrometry analysis were summed to assess daily overall cortisol (ΣC21) and adrenal androgen secretion; urinary free cortisol and cortisone measured by RIA were summed (UFF+UFE) as an indicator of potentially bioactive free glucocorticoids. Main Outcomes: The main outcomes included ATO, age at peak height velocity, age at menarche/voice break, ages at Tanner stage 2 for breast (girls) and genital (boys) development, and pubic hair. Results: In girls ΣC21, but not UFF+UFE, was associated with pubertal markers after adjusting for overall adrenal androgen, urinary nitrogen, and body fat. Girls with higher ΣC21 (fourth quartile) reached ATO 0.7 yr (P = 0.01) and menarche 0.9 yr later (P = 0.006) than girls with lower ΣC21 (first quartile). The ΣC21 tended to be also positively associated with age at Tanner stage 2 for breast (P = 0.1), Tanner stage 2 for pubic hair (P = 0.1), and age at peak height velocity (P = 0.06). In boys, neither the ΣC21 nor UFF+UFE was related to pubertal timing. Conclusion: An individually higher prepubertal glucocorticoid secretion level, even in physiological range, appears to delay early and late pubertal timing of healthy girls, particularly their onset of pubertal growth spurt and menarche.